Long-term changes in floristic diversity, composition and stand structure in Acacia auriculiformis plantation in Mount Makiling Forest Reserve, Philippines (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hernandez JO, Ata JP, Combalicer MS. 2022. Long-term changes in floristic diversity, composition and stand structure in Acacia auriculiformis plantation in Mount Makiling Forest Reserve, Philippines. Biodiversitas 23: 3631-3638. There have been continuous debates about whether exotic tree plantation facilitates vegetation succession. In the Philippines, the potential for the re-establishment of native plant communities and improvement of the plant community structure under exotic tree plantations has not yet been evaluated adequately. Thus, the study investigated the dynamics in floristic diversity, composition and stand structure of a reforested area using Acacia auriculiformis Benth. in Sitio Kay Inglesia, Mount Makiling Forest Reserve (MMFR), Philippines. The changes in basal area, stem density, biomass growth, species diversity, species evenness and richness, and canopy closure were determined between two study periods, i.e., 1993-2008 and 2009-2019. Results revealed significant changes in stem density (i.e., 1324 to 2135 trees ha-1) and canopy closure (i.e., 18% to 10%) for mature trees and seedlings/saplings in 2009-2019. The changes in basal area and aboveground biomass were not significant between the two study periods. The species richness was significantly higher in 2009-2019 (i.e., 55 species) than in 1993-2008 (i.e., 22 species). The species diversity also significantly increased from low (i.e., H' = 1.99, S = 23) to moderate (i.e., H' = 2.88, S = 55). Moreover, the number of exotics decreased (i.e., 60 to 40% or 15 to 9 species) as the number of native ones increased (i.e., 27 to 72% or 15 to 40 species). Therefore, the findings of the present study show that re-establishment of native species is possible when restoring degraded land with A. auriculiformis plantation. However, monitoring studies on other key ecosystem attributes (e.g., ecosystem functionality, external exchanges, structural diversity) of the plantation are recommended to enhance our understanding of the species' potential for restoration.